1996
DOI: 10.1016/s1010-7940(96)80144-8
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life after surgical therapy of bronchogenic carcinoma

Abstract: Quality of life (QL) after the "curative" resection of non-small cell bronchogenic carcinoma was assessed by patients using the EORTC QL questionnaire (QLQ) and by a psychologist using the Spitzer Index. Quality of life was assessed in 52 patients on one occasion 12 months postoperatively and in 20 patients regularly starting with a preoperative assessment. Self- and external evaluation showed a significant correlation (r = 0.41), but QL was assessed as being higher by the external observer. After surgery it w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
1
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 2 publications
5
47
1
5
Order By: Relevance
“…(20) The authors found that, compared with preoperative values, QoL is lower in the immediate postoperative period but is restored by that pulmonary function worsened in all of the patients evaluated (Table 1).…”
Section: Discussionmentioning
confidence: 88%
“…(20) The authors found that, compared with preoperative values, QoL is lower in the immediate postoperative period but is restored by that pulmonary function worsened in all of the patients evaluated (Table 1).…”
Section: Discussionmentioning
confidence: 88%
“…Zieren et al 12 assessed QoL in 20 lung cancer patients 1 day before surgery, postoperatively on the day of discharge from hospital and at 3-month intervals thereafter until the end of the first postoperative year (6 times) using the EORTC QLQ-C30. The external evaluation was made by a psychologist using the Spitzer Index.…”
Section: Discussionmentioning
confidence: 99%
“…Dales and colleagues [12] reported that HRQOL deteriorated early after thoracotomy and returned to preoperative status since 6 months postoperatively. Zieren and colleagues [11] also reported that the postoperative deterioration of HRQOL was mainly affected by restrictions related to physical activities, job and household tasks, and disease symptoms, while limitations in emotional and social domains were less frequent and less severe. In addition, Nou and Aberg [23] reported that HRQOL was better in 5-year surviving patients and poorer in those receiving nonresectional thoracotomy.…”
Section: Commentmentioning
confidence: 97%
“…Health-related quality of life is one of the primary outcome measures in evaluating LVR and is now recognized as an important measure also in patients with lung cancer [11][12][13].…”
mentioning
confidence: 99%
See 1 more Smart Citation